Causes of death up to 10 years after admissions to hospitals for self-inflicted, drug-related or alcohol-related, or violent injury during adolescence: a retrospective, nationwide, cohort study. Issue 10094 (5th August 2017) - Herbert, Annie; Gilbert, Ruth; Cottrell, David; Li, Leah
Summary: Background: Emergency hospital admission with adversity-related injury (ie, self-inflicted, drug-related or alcohol-related, or violent injury) affects 4% of 10–19-year-olds. Their risk of death in the decade after hospital discharge is twice as high as that of adolescents admitted to hospitals for accident-related injury. We established how cause of death varied between these groups. Methods: We did a retrospective, nationwide, cohort study comparing risks of death in five causal groups (suicide, drug-related or alcohol-related, homicide, accidental, and other causes of death) up to 10 years after hospital discharge following adversity-related (self-inflicted, drug-related or alcohol-related, or violent injury) or accident-related (for which there was no recorded adversity) injury. We included adolescents (aged 10–19 years) who were admitted as an emergency for adversity-related or accident-related injury between April 1, 1997, and March 31, 2012. We excluded adolescents who did not have their sex recorded, died during the index admission, had no valid discharge date, or were admitted with injury related to neither adversity nor accidents. We identified admissions for adversity-related or accident-related injury to the National Health Service in England with the International Classification of Diseases-10 codes in Hospital Episode Statistics data, linked to the Office for National Statistics mortality data for England, to establish cause-specific risks of death between the first day and 10 years after discharge, and to compare risks between adversity-related and accident-related index injury after adjustment for age group, socioeconomic status, and chronic conditions. Findings: We identified 1 080 368 adolescents (388 937 [36·0%] girls, 690 546 [63·9%] boys, and 885 [0·1%] adolescents who did not have their sex recorded). Of these adolescents, we excluded 40 549 (10·4%) girls, 56 107 (8·1%) boys, and all 885 without their sex recorded. Of the 333 009 (30·8%) adolescents admitted with adversity-related injury (181 926 [54·6%] girls and 151 083 [45·4%] boys) and 649 818 (60·2%) admitted with accident-related injury (166 462 [25·6%] girls and 483 356 [74·4%] boys), 4782 (0·5%) died in the 10 years after discharge (1312 [27·4%] girls and 3470 [72·6%] boys). Adolescents discharged after adversity-related injury had higher risks of suicide (adjusted subhazard ratio 4·54 [95% CI 3·25–6·36] for girls, and 3·15 [2·73–3·63] for boys) and of drug-related or alcohol-related death (4·71 [3·28–6·76] for girls, and 3·53 [3·04–4·09] for boys) in the next decade than they did after accident-related injury. Although we included homicides in our estimates of 10-year risks of adversity-related deaths, we did not explicitly present these risks because of small numbers and risks of statistical disclosure. There was insufficient evidence that girls discharged after adversity-related injury had increased risks of accidental deaths compared with those discharged after accident-related injury (adjusted subhazard ratio 1·21 [95% CI 0·90–1·63]), but there was evidence that this risk was increased for boys (1·26 [1·09–1·47]). There was evidence of decreased risks of other causes of death in girls (0·64 [0·53–0·77]), but not in boys (0·99 [0·84–1·17]). Risks of suicide were increased following self-inflicted injury (adjusted subhazard ratio 5·11 [95% CI 3·61–7·23] for girls, and 6·20 [5·27–7·30] for boys), drug-related or alcohol-related injury (4·55 [3·23–6·39] for girls, and 4·51 [3·89–5·24] for boys), and violent injury in boys (1·43 [1·15–1·78]) versus accident-related injury. However, the increased risk of suicide in girls following violent injury versus accident-related injury was not significantly increased (adjusted subhazard ratio 1·48 [95% CI 0·73–2·98]). Following each type of index injury, risks of suicide and risks of drug-related or alcohol-related death were increased by similar magnitudes. Interpretation: Risks of suicide were significantly increased after all types of adversity-related injury except for girls who had violent injury. Risks of drug-related or alcohol-related death increased by a similar magnitude. Current practice to reduce risks of harm after self-inflicted injury should be extended to drug-related or alcohol-related and violent injury in adolescence. Prevention should address the substantial risks of drug-related or alcohol-related death alongside risks of suicide. Funding: UK Department of Health.